In Vitro and Ex Vivo Models for Screening Topical Anti-Inflammatory Drugs - Juan Luis Pérez-Salas; Martha Rocío Moreno-Jiménez; Nuria Elizabeth Rocha-Guzmán; Rubén Francisco González-Laredo; Luis Medina-Torres; José Alberto Gallegos-Infante (MDPI AG, 2023)
Skin inflammation occurs as an immune response to various stimuli such as ultraviolet light, irritants, or any type of skin barrier injury. Finding safe and effective drugs to combat skin inflammation remains a research challenge. Ethical and legal considerations in animal testing encourage the development of in vitro and ex vivo models for the detection of skin inflammation. This report presents an updated review of non-animal study models available for screening drugs with anti-inflammatory potential. It includes a description of the basic methods used to inhibit protein denaturation and red blood cell membrane stability. Three in vitro inhibition assay methods for enzymes relevant to the skin inflammatory process are then described. The development of cell culture models is described: relatively simple and easy-to-produce two-dimensional (2D) skin cell cultures that allow assessment of response to a given stimulus, three-dimensional (3D) cell cultures that better mimic human skin physiology by more accurately replicating mechanical and chemical signals, and vascularized 3D skin models with dynamic perfusion and microfluidic devices known as skin on a chip. Finally, ex vivo skin models are presented that could more accurately represent human skin in terms of structure, cell signaling mechanisms, and absorption effects. Although the current development of models without the use of animals is promising, improvements and refinements are needed to make the models more suitable as screening platforms for topical anti-inflammatory drugs.